Can Microfiltered Seminal Plasma Preserve the Morphofunctional Characteristics of Porcine Spermatozoa in the Absence of Antibiotics? A Preliminary Study. (13th May 2016) - Barone, F; Ventrella, D; Zannoni, A; Forni, M; Bacci, ML
Contents: Artificial insemination is extensively performed in pig farms in Europe, the United States and Canada. Antibiotics are typically added to the inseminating dose to limit bacterial growth during liquid phase storage at 16°C, as bacterial contamination is unavoidable. The World Organization for Animal Health (OIE) and the Food and Agriculture Organization (FAO) take action to control and reduce antibiotic use in animals as more bacteria are becoming resistant to antimicrobials. To avoid the use of antibiotics, we prepared inseminating doses using microfiltered seminal plasma (SP). Microfiltration is a common technology used to reduce bacterial contamination but may retain seminal substances, influencing sperm quality during storage. Therefore, the aim of this study was to evaluate the morphofunctional parameters of spermatozoa during storage at 16°C in doses prepared with or without microfiltered SP, with or without the addition of antibiotics, in a Latin square design. Artificial insemination doses with microfiltered SP and without antibiotic addition preserved spermatozoa viability, mitochondrial membrane potential, acrosome integrity and objective motility, with absolute values equal or even better than those observed in conventional doses. In conclusion, although the results could be considered preliminary due to the small sample size, this study suggests that microfiltration of SP can be a simple method, feasible on farms, to replace antibiotic use in extended doses stored in the liquid phase at 16°C for up to 7 days.